Innovativeness as a Determinant of Territorial Development - Łuszczyszyn, Andrzej; Papież, Patrycja (Innowacyjność jako determinanta rozwoju ukierunkowanego terytorialnie, 2023)
Innovativeness is a key determinant in territorial development. Due to the fact that this development is concentrated on a specific geographical area, it refers to the ability to introduce novel, unique solutions, but above all to make use of knowledge and create new value in a given territory. Undeniably, it has an influence not only on the creation of a competitive advantage, economic growth, and the development of strategic sectors, but also, which should be underlined, on cooperation and clustering. The need to implement innovations stems from the competitiveness of enterprises, but above all, from the need to stimulate a territory as a specific social structure. For this reason, in the current socio-economic reality, innovativeness refers to the whole community in a given territory, its history, culture, knowledge and territorial capital skills. The aim of the article was to analyse the opportunities for implementing innovative processes in order to strengthen the territorial development paradigm, which is as yet poorly understood and popularised in the economic sciences, although sometimes correctly associated with the development of socio-economic areas (regions, micro-regions). The article is theoretical in nature. The research method applied is critical analysis of the subject literature.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 48-55
Keywords: innovativeness; innovation; territory; territorial development; innowacyjność; innowacje; terytorium; rozwój terytorialny